2006
DOI: 10.4321/s1130-14732006000600002
|View full text |Cite
|
Sign up to set email alerts
|

Valor predictivo de la clasificación de Knosp en el grado de resección quirúrgica de los macroadenomas invasivos: Estudio prospectivo de una serie de 23 casos

Abstract: The Knosp classification alone cannot predict the behavior of these tumors. In our experience, despite tumor extension to the cavernous sinus, pituitary macroadenomas can be safely resected with low morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…So, although the volume is an important factor to consider in the surgical planning, the SIPAP extension and Knosp invasion grades could give more information about the possible extent of resection, which is described by many authors. 12,13,15,16,19,20,21,22 Knosp grade of invasion of the cavernous sinus is widely described as one of the most important factors to consider before pituitary adenoma surgery, being unfavorable as the grade goes higher. This invasion represents a negative prognostic factor, reducing the probability of success in surgical treatment, both in terms of complete tumor resection and hormonal remission in functioning tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So, although the volume is an important factor to consider in the surgical planning, the SIPAP extension and Knosp invasion grades could give more information about the possible extent of resection, which is described by many authors. 12,13,15,16,19,20,21,22 Knosp grade of invasion of the cavernous sinus is widely described as one of the most important factors to consider before pituitary adenoma surgery, being unfavorable as the grade goes higher. This invasion represents a negative prognostic factor, reducing the probability of success in surgical treatment, both in terms of complete tumor resection and hormonal remission in functioning tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This invasion represents a negative prognostic factor, reducing the probability of success in surgical treatment, both in terms of complete tumor resection and hormonal remission in functioning tumors. 12,13 Dallapiaza et al found that tumors with Knosp grades 0 to 2 and volumes up to 10 cm 3 had more chance to get a gross total resection, being Knosp grade the only independent predictor in a multivariate analysis. 21 In our study, Knosp had a correlation with the extent of resection, but it didn't result as an independent predictor in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation